Lettere di Polianzio ad Ermogene intorno alla traduzione dell'Eneide del Caro - Algarotti, Francesco (Biblioteca di Studi di Filologia Moderna, 2022)
Martina Romanelli holds a PhD in Philology, Italian Literature, and Linguistics. She is a member of the editorial board working on the correspondence of Francesco Algarotti. She also edited Saggio sopra la rima and Nereidologia (2021). Her research interests are mainly focused on Giacomo Leopardi, Piero Bigongiari, Mario Luzi and Giuseppe Dessí.